2021
DOI: 10.1111/jfs.12919
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of viruses using nonthermal plasma in viral suspensions and foodstuff: A short review of recent studies

Abstract: This review tries to introduce the novel and promising technology of the nonthermal plasma against different viruses and virus surrogates, which can trigger food infections and gastroenteritis. It has been reported that the noroviruses are responsible for 21 million cases of gastrointestinal illness annually just in the United States. The article is divided into the introduction for nonthermal plasma, its antiviral mechanism, and the most effective parameters on its antiviral functionality. This technology off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Surface contagion can pose a high risk of transmission as the infectious virions can stay viable on various surfaces (e.g., plastic, metals, and cardboard) for several hours [ 2 , 3 ]. Several traditional sterilization processes (sodium hypochlorite, soap water, steam, dry heat, alcohol, and UV) used for the surface decontamination have numerous shortcomings, and inventive methods are required for the virus inactivation [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surface contagion can pose a high risk of transmission as the infectious virions can stay viable on various surfaces (e.g., plastic, metals, and cardboard) for several hours [ 2 , 3 ]. Several traditional sterilization processes (sodium hypochlorite, soap water, steam, dry heat, alcohol, and UV) used for the surface decontamination have numerous shortcomings, and inventive methods are required for the virus inactivation [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many experiments have shown that plasmas can effectively kill viruses or reduce their infectivity [10,11]. In 1999, Kelly-Wintenberg and colleagues published the first paper relating to the inactivation of viral microorganisms by plasma [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of plasma technology, plasma has proved to be effective in killing bacteriophages, human adenovirus, HIV and many other viral microorganisms [12][13][14][15]. In the current global COVID-19 pandemic, the application of plasma to reduce the infectivity of SARS-CoV-2 and control the outbreak has become a hot topic.…”
Section: Introductionmentioning
confidence: 99%
“…The disinfection effects of NTP have been studied mainly on bacteria, but attempts to inactivate viruses [39][40][41] or fungi both in vitro and in vivo [42,43] were also made. In general, the sensitivity of various microbes to NTP differs substantially: while the inactivation of bacteria is complete within seconds to minutes, yeasts require exposure for several minutes and mold and bacterial spores several tens of minutes.…”
Section: Introductionmentioning
confidence: 99%